Chronic Posttraumatic Stress Disorder and Comorbid Cognitive and Physical Impairments in World Trade Center Responders. Issue 3 (21st November 2020) - Diminich, Erica D.; Clouston, Sean A. P.; Kranidis, Alexandra; Kritikos, Minos; Kotov, Roman; Kuan, Peifen; Carr, Melissa; Bromet, Evelyn J.; Luft, Benjamin J.
Abstract: Posttraumatic stress disorder (PTSD) has been linked to increased prevalence and incidence of cognitive and physical impairment. When comorbid, these conditions may be associated with poor long‐term outcomes. We examined associations between chronic PTSD and symptom domains with cognitive and physical functioning in World Trade Center (WTC) responders nearly 20 years after the September 11, 2001, terrorist attacks. Participants included a cross‐sectional sample of 4, 815 responders who attended a monitoring program in 2015–2018. Montreal Cognitive Assessment scores less than 23 indicated cognitive impairment (CogI); Short Physical Performance Battery scores 9 or lower on a hand‐grip test indicated physical impairment (PhysI). Comorbid cognitive/physical impairment (Cog/PhysI) was defined as having cognitive impairment with at least one objective PhysI indicator. Clinical chart review provided PTSD diagnoses; symptom domains were assessed using the PTSD Checklist. Participants were on average 53.05 years ( SD = 8.01); 13.44% had PTSD, 7.8% had CogI, 24.8% had PhysI, and 5.92% had comorbid Cog/PhysI. Multivariable‐adjusted multinomial logistic regression demonstrated that Responders with PTSD have more than three times the risk of Cog/PhysI (adjusted RR = 3.29, 95% CI 2.44‐ 4.44). Domain‐specific analyses revealed that emotional numbing symptoms predicted an increased risk of PhysI (adjusted RR = 1.57, 95% CI 1.08‐2.28), whereas reexperiencing symptoms were associated with comorbid Cog/PhysI (adjusted RR = 3.96, 95% CI, 2.33‐6.74). These results suggest that responders with chronic PTSD may have increased risk of deficits beyond age‐expected impairment characterized by the emergence of comorbid Cog/PhysI at midlife. 簡體及繁體中文撮要由亞洲創傷心理研究學會翻譯: JOTS‐20‐0075.R2_Clouston_Cantonese Traditional Chinese 世貿中心急救人員的慢性創傷後壓力症及共病認知/身體障礙 摘要: 創傷後壓力症(PTSD)與認知和身體損傷的流行率和發生率增加有關。當共病時, 這些情況可能與不良的長期結果有關。 2001年9月11日恐怖襲擊發生近20年後, 我們在世貿中心(WTC)急救人員中研究了慢性創傷後壓力症和症狀領域與認知和身體功能之間的聯繫。參與者包括2015‐2018年參加監測項目的4, 815名反應者的橫斷面樣本。蒙特利爾認知評估得分低於23分表示有認知障礙(CogI);短距離體能測試得分低於9分表示有身體障礙(PhysI)。共病認知/身體障礙(CogPhysI)定義為至少有一個客觀的PhysI指標的認知損害。臨床病歷審查提供了創傷後壓力症的診斷;使用創傷後壓力症檢查表評估症狀領域。參與者平均53.05歲(SD=8.01);13.44%患有創傷後壓力症, 7.8%患有認知障礙, 24.8%患有身體障礙, 及5.92%患有共病認知/身體障礙。經多變量調整的多項邏輯回歸顯示, 有創傷後壓力症的應答者患認知/身體障礙的風險是三倍以上(調整後RR=3.29, 95%CI為2.44‐4.44)。特定領域的分析顯示, 情緒麻木症狀預示著身體障礙的風險增加(調整後的RR=1.57, 95%CI 1.08‐2.28), 而重新體驗症狀與共病認知/身體障礙有關(調整後的RR=3.96, 95%CI, 2.33‐6.74)。這些結果表明, 慢性創傷後壓力症臨床治療者的缺陷風險高於年齡預期損傷, 這是一種多系統疾病, 以中年時出現並存的認知/身體障礙為特徵。 Simplified Chinese 世贸中心急救人员的慢性创伤后压力症及共病认知/身体障碍 摘要: 创伤后压力症(PTSD)与认知和身体损伤的流行率和发生率增加有关。当共病时, 这些情况可能与不良的长期结果有关。 2001年9月11日恐怖袭击发生近20年后, 我们在世贸中心(WTC)急救人员中研究了慢性创伤后压力症和症状领域与认知和身体功能之间的联系。参与者包括2015‐2018年参加监测项目的4, 815名反应者的横断面样本。蒙特利尔认知评估得分低于23分表示有认知障碍(CogI);短距离体能测试得分低于9分表示有身体障碍(PhysI)。共病认知/身体障碍(CogPhysI)定义为至少有一个客观的PhysI指标的认知损害。临床病历审查提供了创伤后压力症的诊断;使用创伤后压力症检查表评估症状领域。参与者平均53.05岁(SD=8.01);13.44%患有创伤后压力症, 7.8%患有认知障碍, 24.8%患有身体障碍, 及5.92%患有共病认知/身体障碍。经多变量调整的多项逻辑回归显示, 有创伤后压力症的应答者患认知/身体障碍的风险是三倍以上(调整后RR=3.29, 95%CI为2.44‐4.44)。特定领域的分析显示, 情绪麻木症状预示着身体障碍的风险增加(调整后的RR=1.57, 95%CI 1.08‐2.28), 而重新体验症状与共病认知/身体障碍有关(调整后的RR=3.96, 95%CI, 2.33‐6.74)。这些结果表明, 慢性创伤后压力症临床治疗者的缺陷风险高于年龄预期损伤, 这是一种多系统疾病, 以中年时出现并存的认知/身体障碍为特征。